Compound Energy Storage System and Energy Management Strategy for Pure Electric Bus - ZHOU Mei-lan; LIU Jun-peng; YANG Ming-liang (Journal of Harbin University of Science and Technology)
Given the excessive battery power in the composite energy storage system，two power allocationcontrol strategies were developed，namely，fuzzy control strategy and the filter control strategy. The vehicle model was constructed based on the MATLAB-CＲUISE， and simulation is carried out in the urban road conditions in China and urban road conditions in Harbin respectively. The power curve of the composite energy storage system，the change curve of the state of charge and the current distribution curve of the battery with fuzzy control strategy and filter control strategy are given. Simulation results show that compared with the filter control strategy，the fuzzy control strategy improves SOC ( state of charge) of the battery by 0. 062% ， the energy saving is 1. 160 3 kW·h and the maximum output power is reduced by 0. 82 kW in the urban road conditions in China. Compared with the filter control strategy，the fuzzy control strategy improves SOC of the battery by 0. 125% ， reduces energy consumption by 1. 682 5 kW·h and the maximum output power is reduced by 0. 99 kW in the urban road conditions in Harbin. The simulation and results show that proposed the fuzzy control strategy of composite energy storage system can reduce the output power of the battery and recover braking energy effectively.